Design and testing of a positioning system based on a quasi kinematic guide and a clamp plate suspended by compliant straps for in-line metrology systems. (April 2020) - Guamán-Lozada, Darío; Ahuett-Garza, Horacio; Castro-Martin, Ana Pamela; Ruiz-Carrizal, Julio; Márquez-Alderete, Maria Fernanda; Anaya-Aranda, José Gustavo; Kurfess, Thomas R.; González de Castilla, Emilio
Highlights: A novel design for a guiding – positioning system for an increasingly important application in manufacturing has been presented. Design offers a solution to the need for quick and accurate part positioning for in-line metrology, an emerging trend in metal making applications. A novel quasi kinematic guide system was introduced. Tests in the field and lab conditions showed that the system is capable of delivering an excellent repeatability. Characterization of the compliant strap design is a topic for further research that can help expand its applications. Abstract: Full inspection of parts in production lines has emerged as an alternative to validate compliance of products with target specifications. Quick and accurate workpiece setup is critical for reliable measuring operations. This article introduces a design for quick, accurate fixturing of parts for in-line metrology. The design includes quasi-kinematic couplings that direct and position parts at the end of the stroke of a linear actuator, and a set of compliant straps to hold parts in place. Tests show the system is capable of positioning parts with excellent repeatabilities, at rates that allow the measuring process to keep up with production.